2014
DOI: 10.1007/s00425-014-2166-3
|View full text |Cite
|
Sign up to set email alerts
|

The B-ring hydroxylation pattern of anthocyanins can be determined through activity of the flavonoid 3′-hydroxylase on leucoanthocyanidins

Abstract: In contrast to current knowledge, the B -ring hydroxylation pattern of anthocyanins can be determined by the hydroxylation of leucoanthocyanidins in the 3' position by flavonoid 3'-hydroxylase. The cytochrome P450-dependent monooxygenases flavonoid 3'-hydroxylase (F3'H) and flavonoid 3',5'-hydroxylase (F3'5'H) are key flavonoid enzymes that introduce B-ring hydroxyl groups in positions 3' or 3' and 5', respectively. The degree of B-ring hydroxylation is the major determinant of the hue of anthocyanin pigments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…WAT11 cells transformed with pYES-DEST52- CsF3 ′ H vector catalyzed the hydroxylation at B-ring 3′-position of naringenin, dihydrokaempferol and kaempferol to eriodictyol, dihydroquercetin and quercetin, respectively, which indicates a broad substrate specificity of CsF3′H. In a recent report [ 36 ] leucopelargonidin was demonstrated to be also a substrate for F3′H. Due to the limited availability of the substrate, this compound was not covered in the present study.…”
Section: Resultsmentioning
confidence: 97%
“…WAT11 cells transformed with pYES-DEST52- CsF3 ′ H vector catalyzed the hydroxylation at B-ring 3′-position of naringenin, dihydrokaempferol and kaempferol to eriodictyol, dihydroquercetin and quercetin, respectively, which indicates a broad substrate specificity of CsF3′H. In a recent report [ 36 ] leucopelargonidin was demonstrated to be also a substrate for F3′H. Due to the limited availability of the substrate, this compound was not covered in the present study.…”
Section: Resultsmentioning
confidence: 97%
“…The resulting pigments are stored in the vacuoles (Matern et al 1986). The hydroxylation pattern of the B-ring can be established at different intermediate levels (Schwinn et al 2014). The synthesis of Cy-derivatives includes a hydroxylation step at the 3 0 -position by F3 0 H, whereas the formation of Dp-based pigments ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the expression of c73764_g1_i1 and c74095_g3_i1 based on transcriptome data showed that the expression of c73764_g1_i1 in the red culm was higher than that in the leaf. F3′H (EC 1.14.13.21) transforms dihydroflavonol into dihydroquercetin by adding a hydroxyl to the 3' position of ring B (Schwinn et al, 2014). The transcriptome data indicated the existence of five F3′H-encoding genes.…”
Section: Transcriptome-based Analysis Of Differentially Expressed Genesmentioning
confidence: 99%